A polyphasic taxonomy analysis reveals the presence of an ecotype of Rahnella contaminans associated with the gut of Dendroctonus-bark beetles - Rivera-Orduña, Flor N.; Pineda-Mendoza, Rosa María; Vega-Correa, Brenda; López, María Fernanda; Cano-Ramírez, Claudia; Zhang, Xiao Xia; Chen, Wen Feng; Zúñiga, Gerardo (Frontiers in Microbiology, 2023)
Species belonging to the genus Rahnella are dominant members of the core gut bacteriome of Dendroctonus-bark beetles, a group of insects that includes the most destructive agents of pine forest in North and Central America, and Eurasia. From 300 isolates recovered from the gut of these beetles, 10 were selected to describe an ecotype of Rahnella contaminans. The polyphasic approach conducted with these isolates included phenotypic characteristics, fatty acid analysis, 16S rRNA gene, multilocus sequence analyses (gyrB, rpoB, infB, and atpD genes), and complete genome sequencing of two isolates, ChDrAdgB13 and JaDmexAd06, representative of the studied set. Phenotypic characterization, chemotaxonomic analysis, phylogenetic analyses of the 16S rRNA gene, and multilocus sequence analysis showed that these isolates belonged to Rahnella contaminans. The G + C content of the genome of ChDrAdgB13 (52.8%) and JaDmexAd06 (52.9%) was similar to those from other Rahnella species. The ANI between ChdrAdgB13 and JaDmexAd06 and Rahnella species including R. contaminans, varied from 84.02 to 99.18%. The phylogenomic analysis showed that both strains integrated a consistent and well-defined cluster, together with R. contaminans. A noteworthy observation is the presence of peritrichous flagella and fimbriae in the strains ChDrAdgB13 and JaDmexAd06. The in silico analysis of genes encoding the flagellar system of these strains and Rahnella species showed the presence of flag-1 primary system encoding peritrichous flagella, as well as fimbriae genes from the families type 1, α, β and σ mainly encoding chaperone/usher fimbriae and other uncharacterized families. All this evidence indicates that isolates from the gut of Dendroctonus-bark beetles are an ecotype of R. contaminans, which is dominant and persistent in all developmental stages of these bark beetles and one of the main members of their core gut bacteriome.